PENGARUH KETERAMPILAN, PENGETAHUAN DAN KEMAMPUAN SUMBER DAYA MANUSIA TERHADAP KINERJA UMKM DI KECAMATAN KERUAK LOMBOK TIMUR - Hanisa, Hanisa; Daeng, Akung; Astusi, Endang (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
The aim of this research is to examine and analyze the influence of HR skills, knowledge and abilities on the performance of MSMEs in Keruak District, East Lombok. This research is a descriptive research. The research method used is a quantitative research method. The population in this research are micro business actors in Keruak District, East Lombok. The sampling technique used a purposive sampling method and a research sample of 96 respondents was obtained. For the data analysis method, use the Multiple Linear Regression Analysis method. The results of this research show that the results of hypothesis testing show that the t value is > (1.986) t table, namely the skills variable is 3.487, the knowledge variable is 2.154 and the ability variable is 2.055 so it can be concluded that skills, knowledge and abilities have a significant effect on the performance of MSMEs in the District. Keruak, East Lombok Regency. And simultaneously the research results show that the variables of skill, knowledge and ability simultaneously have a significant effect on the performance of MSMEs in Keruak District, East Lombok Regency with a calculated F value (12,524) > F table (2.70).